PENGARUH PELAYANAN DAN PENGETAHUAN TERHADAP MINAT NASABAH MENGGUNAKAN TABUNGAN MUDHARABAH KSPPS BMT AL-HIJRAH BUKITINGGI - Winda Fauzia; Amsah Hendri Doni (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Customer interest in using mudharabah savings has decreased because customers do not understand the concept of sharia in mudharabah savings, it is seen that the service by KSPPS BMT Al-hijrah Bukittinggi is good but customers are still not interested in using mudharabah savings lack of interest in using mudharabah savings due to pick-up serviceemployees are given different service procedures in serving customers and the knowledge provided by KSPPS BMT Al-hijrah Bukitinggi employees is in accordance with the standard operational procedures, but customers are not interested in using mudharabah savings.This study is intended to measure the influence of service and knowledge simultaneously on customer interest in using KSPPS BMT Al-hijrah Bukittinggi mudharabah savings. The type of research used is quantitative descriptive research. The data used are primary data and secondary data. The respondents in the study were customers who used mudharabah savings sample of 93 respondents who used data collection techniques by observation, questionnaire distribution, and literature study. The data processing technique used a research instrument test consisting of validity and reliability test, a classical assumption test consisting of (normality test, autocorrelation test, multicollinearity test and heteroscedasticity test), multiple linear regression analysis, determination coefficient test, hypothesis test consisting of t test and f test. The results of this study show that partially the service has a value of 0.014 less than 0.05 or (0.014 < 0.05) thus it can be concluded that the service variable has a partial effect on interest, knowledge 0.000 is less than 0.05 or (0.000 < 0.05) thus it can be concluded that the knowledge variable has a partial effect on interest. Simultaneously service and knowledge have a value of F calculated > F table or 69,680 > 3,947, thus it can be concluded that service and knowledge together significantly affect interest.